A possible critical heating from decay reaction and new upper limit of the magnetic monopole flux for the supermassive white dwarfs - Jing-Jing Liu; Dong-Mei Liu (European Physical Journal C: Particles and Fields, 2024)
Abstract We present the new upper limit of the magnetic monopole (MM) flux and discuss three MM models of the heating resource for supermassive white dwarfs (WDs) by considering the effect of temperature on thermonuclear reaction and mass radius relation of WDs based on the catalytic nuclear decay by MM. We discuss the luminosity and compared it with the observations to apply to 25 supermassive WDs. We find the maxnium of the number of MM captured can be $$9.6943× 10^{11}$$ 9.6943 × 10 11 , and $$9.0671× 10^{11}$$ 9.0671 × 10 11 for O+Ne core high mass WDs (e.g., WD J055631.17+130639.78), and C+O core high mass WDs (e.g., WD J055631.17+130639.78), respectively. The luminosities increase with the increasing of the temperature and are agreed well with the observations for model (III). The differences are no more than one, and three orders of magnitude higher than observations for model (III), and (I, II), respectively. Finaly, we find that the maxnium of the upper limits of the MM flux $$φ _{m}$$ ϕ m due to RC effect can be $$9.1071× 10^{-15}$$ 9.1071 × 10 - 15 , and $$2.7670× 10^{-14}$$ 2.7670 × 10 - 14 for O+Ne and C+O core high mass WDs, respectively. Our results are about one and two orders of magnitude higher than those of Abbasi et al. (EPJC 69:361, 2010) (Albert et al. in JHEP 07:054, 2017) for O+Ne, and C+O core mass WDs, respectively, and can be about three and four orders of magnitude higher than those of Aartsen et al. (EPJC 76:133, 2016) (Ic40, Ic86), respectively. Our results show that the monopole-catalyzed nucleon decay could prevent WDs from cooling down into a stellar graveyard by keeping them hot.